The significance of heart failure in hospitalised patients with pulmonary embolism. A gender‐specific analysis. Issue 10 (7th July 2021) - de‐Miguel‐Diez, Javier; López‐de‐Andrés, Ana; Hernandez‐Barrera, Valentín; Jimenez, David; Monreal, Manuel; López‐Herranz, Marta; Ji, Zichen; Jiménez‐García, Rodrigo
Abstract: Background: Heart failure (HF) is a risk factor for the development of pulmonary embolism (PE). Few studies have examined sex differences in risk of PE among HF patients. Aims: (a) To examine the incidence, characteristics and in‐hospital outcomes among patients hospitalised with PE according to HF status; (b) to compare the in‐hospital mortality (IHM) after PE between HF and non‐HF patients and (c) to identify variables associated with IHM. All analyses were stratified by sex. Methods: We included all adult patients hospitalised for PE from 1 January 2016 to 31 December 2018. Data were collected from the Spanish National Hospital Discharge Database. Poisson regression models were constructed to quantify the difference in the incidences between HF and non‐HF populations. Propensity score matching (PSM) was used to obtain comparable subgroups by sex and HF status. Results: We identified 46, 835 PE hospitalisations, 11.4% with HF. Adjusted incidence of PE was higher in HF patients than in those without HF (Incidence Rate Ratio 1.11; 95% CI 1.08‐1.13). Crude and PSM adjusted IHM were significantly higher in men and women hospitalised with PE suffering HF than in men and women without HF ( P < .001). Women with HF who suffered a PE had lower IHM than men with this condition ( P < .001) after adjusting. Conclusions: Adjusted incidence of PE was higher in HF patients than in those without HF. After PSM suffering, HF was associated to higher IHM in men and women. Women with PE and HF had lower IHM than men with these conditions.